Ikebana : the Zen way of flowers - Ueno, Yuji (Tuttle Publishing, 2023)
It's all about light, texture, colour, shape and balance! Filled with inspiring images of unconventional flower arrangements, this new book by Japanese Ikebana master Yuji Ueno shows you how to use light and position as well as colour, shape and texture - of both flowers and vessel - to make inexpensive floral arrangements that convey a Zen sense of simplicity, calm and balance.